Genomic and Molecular Characterization of Wheat Streak Mosaic Virus Resistance Locus 2 (Wsm2) in Common Wheat (Triticum aestivum L.) - Xie, Yucong; Nachappa, Punya; Nalam, Vamsi J.; Pearce, Stephen (Frontiers in Plant Science, 2022)
Wheat streak mosaic virus is an economically important viral pathogen that threatens global wheat production, particularly in the Great Plains of the United States. The Wsm2 locus confers resistance to WSMV and has been widely deployed in common wheat varieties adapted to this region. Characterizing the underlying causative genetic variant would contribute to our understanding of viral resistance mechanisms in wheat and aid the development of perfect markers for breeding. In this study, linkage mapping in a doubled-haploid mapping population confirmed Wsm2 as a major locus conferring WSMV resistance in wheat. The Wsm2 flanking markers were mapped to a 4.0 Mbp region at the distal end of chromosome 3BS containing 142 candidate genes. Eight haplotypes were identified from seventeen wheat genotypes collected from different agroecological zones, indicating that Wsm2 lies in a dynamic region of the genome with extensive structural variation, and that it is likely a rare allele in most available genome assemblies of common wheat varieties. Exome sequencing of the variety ‘Snowmass,’ which carries Wsm2, revealed several loss-of-function mutations and copy number variants in the 142 candidate genes within the Wsm2 interval. Six of these genes are differentially expressed in 'Snowmass’ compared to ‘Antero,’ a variety lacking Wsm2, including a gene that encodes a nucleotide-binding site leucine-rich repeat (NBS-LRR) type protein with homology to RPM1. A de novo assembly of unmapped RNA-seq reads identified nine transcripts expressed only in ‘Snowmass,’ three of which are also induced in response to WSMV inoculation. This study sheds light on the variation underlying Wsm2 and provides a list of candidate genes for subsequent validation.